Poetički prijenos: "Pričice" Fedora Sologuba - Benčić, Živa (2012)
In the article, "Little Fairy Tales" by Fedor Sologub are analyzed as an instance of poetic transfer of narrative folklore to artistic literature. However, I do not study transfer of specific images and motifs, but rather transfer of structural principles. In the centre of my interest are those Sologub’s texts which can be characterized as minimalist. The minimalist tendencies of Sologub’s "Little Fairy Tales" I have in mind are not expressed only in the stories’ shortness, but also in reductionist techniques that simplify their narrative structure to a significant extent. In these simplifications, which primarily concern those of the narrator, character and plot, Sologub most frequently looks up to the poetics of the Russian folk tale. By transferring reductionist devices from narrative folklore to his little fairy tales, he in fact attempts to renew the irrational, mythical experience of the world which he considers much more acceptable and true than the contemporary realistic-scientific interpretation of reality.
HRV